Systematic Review: Anti-Forensic Computer Techniques - González Arias, Rafael; Bermejo Higuera, Javier; J. Javier, Rainer Granados; Bermejo Higuera, Juan Ramón; Sicilia Moltalvo, Juan Antonio (Applied Sciences, 2026)
The main purpose of anti-forensic computer techniques, in the broadest sense, is to hinder the investigation of a computer attack by eliminating traces and preventing the collection of data contained in a computer system. Nowadays, cyber-attacks are becoming more and more frequent and sophisticated, so it is necessary to understand the techniques used by hackers to be able to carry out a correct forensic analysis leading to the identification of the perpetrators. Despite its importance, this is a poorly represented area in the scientific literature. The disparity of the existing works, together with the small number of articles, makes it challenging to find one’s way around the vast world of computer forensics. This article presents a comprehensive review of the existing scientific literature on anti-forensic techniques, mainly DFIR (digital forensics incident response), organizing the studies according to their subject matter and orientation. It also presents key ideas that contribute to the understanding of this field of forensic science and details the shortcomings identified after reviewing the state of the art.
Keywords: computer anti-forensic; computer forensic; computer security